Tinjauan Yuridis Perjanjian Kredit Usaha Rakyat Pada Masa Pandemi Covid – 19 : (Studi Di BRI Cabang Gunung Sari) - Janitra Satir Anggradinata; Aris Munandar (Private Law, 2022)
The purpose of this study is to find out the regulation of people's business credit agreement based on Indonesia Civil Code, Act Number 8 of 2015 concerning the Guidelines for the implementation of people's business credit agreement, and find out the People's Business Credit implementation during Covid 19 pandemic. The type of this research is a normative-empirical legal method that uses two types of legal approach method, namely the statute approach and the conceptual approach. The result of this study was that researcher concluded that Circular Letter of the Board of Directors Number SE.22-DIR/KRD/03/2019 concerning Special Treatment of KUR Debtors Affected by Covid-19. The regulation has regulated about People's Business Credit which contains the Criteria for People's Business Credit Debtors and the Decisions on the Restructuring of People's Business Credit.